Plebeian Tribunes and the Government of Early Rome*. (26th October 2017) - Drogula, Fred K.
Abstract: Many modern scholars have argued that the consulship was not created at the foundation of the Republic as Roman tradition maintained, and that the government of the early Republic went through several stages of development before it reached the familiar 'classical constitution.' Building on this work, this article considers what the early civilian government of Rome may have looked like. It is argued that the Romans did not create an entirely new government (based on consuls) following the removal of the monarchy, but instead made use of existing sources of power and authority: rich land-owning clans dominated military activity outside the city, while priests, the curiae, and minor officials exercised responsibilities of civilian governance in Rome. The plebeian tribunate was probably the first significant office to be created in the Republic, and the unusual nature of its power (sacrosanctity) and the absence of any other chief magistracy enabled the tribunes to acquire a broad range of prerogatives. A series of reforms eventually led to the development of the familiar 'classical constitution', and the consulship and praetorship became the most prestigious and desired magistracies (and—outside the city—the most powerful), but the tribunes long retained the broadest prerogatives for civilian governance inside the city.